The emerald atlas [compact disc, unabridged] - Stephens, John, 1972- (Stephens, John, 1972- Books of beginning, 2011)
Kate, Michael, and Emma have passed from one orphanage to another in the ten years since their parents disappeared to protect them, but now they learn that they have special powers, a prophesied quest to find a magical book, and a fearsome enemy.